Evaluation Of Seismic Low Cycle Fatigue On Welded Unreinforced Flange-Welded Web And Reduced Beam Section On Steel Moment Frame - B. Hoseini Kalej; M. Gerami; M. Ghaderi (مهندسی عمران شریف, 2021)
The effect of fatigue on the behavior of steel structures has long been the focus of researchers. However, with the widespread damage of steel structures after the Northridge earthquake, it is important to investigate the issue of low cycle fatigue. The bylaws attempted to address the weaknesses of the connections and introduced prequalified connections. In the present study, the behaviors of two prequalified welded unreinforced flange-welded webs and reduced beam section under low cycle fatigue were investigated. The behavior of high cyclic fatigue was the focus of many researchers, while there is only a limited scope of experimental data available for LCF. In this study, the S-N-curve was used to obtain the Nastar method and available experimental data. This curve was developed using the available experimental results for the low cycle region. Four buildings with different heights were analyzed using linear time history analysis and their behavior under low cycle fatigue was considered. Then, the cumulative fatigue damage was investigated by the Palmgren-Miner fatigue analysis method for the above two connections. Rainflow method was also used for counting cycles. By defining the cumulative fatigue index, for the critical beam of structures, the maximum value of this index was observed at the WUF-W, which was obtained for 0.059 3-storey structure and was increased by 0.24 with the increasing structural height. The index for the critical column in the WUF-W junction in the 15-storey structure was 0.042, while in the other structures, the maximum value was up to 0.197. Also, the fatigue index values for WUF-W binding were higher than those obtained for RBS, indicating that the first connection performance was weaker. Maximum rate of cumulative fatigue index in beams on WUF-W to RBS was 1.29 and for columns, this rate was 1.34. The results indicated the need for greater attention to the effect of low cycle fatigue on connections of steel moment frames, especially on the WUF-W.